Analisis Yuridis Keabsahan Perjanjian Kerja Sama Endorsement dalam Perspektif KUH Perdata - Renti Astuti; Lona Puspita (Fakultas Hukum Universitas Tamansiswa Padang, 2026)
The rapid shift toward a fully digital era has given rise to a form of product marketing collaboration that leverages social media platforms and content creators to promote goods or services through original content. While endorsements have evolved into a practical marketing strategy, the absence of specific regulations creates potential legal issues regarding their validity; thus, this study aims to analyze the forms, validity, and legal consequences of these arrangements—specifically through the lens of the requirements for a valid contract under civil law—to address the existing regulatory gap. Conducted as normative legal research employing statutory and conceptual approaches, the study gathered data via literature review and utilized descriptive analysis. The findings indicate that, under the Indonesian Civil Code, endorsement collaboration agreements are classified as